Proceedings of the 2017 Conference on Empirical Methods in Natural Language Processing 2017
DOI: 10.18653/v1/d17-1090
|View full text |Cite
|
Sign up to set email alerts
|

Question Generation for Question Answering

Abstract: This paper presents how to generate questions from given passages using neural networks, where large scale QA pairs are automatically crawled and processed from Community-QA website, and used as training data. The contribution of the paper is 2-fold: First, two types of question generation approaches are proposed, one is a retrieval-based method using convolution neural network (CNN), the other is a generation-based method using recurrent neural network (RNN); Second, we show how to leverage the generated ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
155
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(156 citation statements)
references
References 17 publications
0
155
0
1
Order By: Relevance
“…While WS-TB is related to the approaches mentioned before, DQG is is also related to question generation (QG). Most of the previous work in QG is in the context of reading comprehension (e.g., Du et al, 2017;Subramanian et al, 2018;Zhao et al, 2018;Du and Cardie, 2018) or QG for question answering (Duan et al, 2017). They substantially differ from our approach because they generate questions based on specific answer spans, while DQG generates a new title from a question's body that can be used as a question duplicate.…”
Section: Duplicates Answers Bodiesmentioning
confidence: 96%
“…While WS-TB is related to the approaches mentioned before, DQG is is also related to question generation (QG). Most of the previous work in QG is in the context of reading comprehension (e.g., Du et al, 2017;Subramanian et al, 2018;Zhao et al, 2018;Du and Cardie, 2018) or QG for question answering (Duan et al, 2017). They substantially differ from our approach because they generate questions based on specific answer spans, while DQG generates a new title from a question's body that can be used as a question duplicate.…”
Section: Duplicates Answers Bodiesmentioning
confidence: 96%
“…Several research have utilized question generation as a tool to improve the efficacy of question answering models [29], [30], [26]. Authors in [30] simultaneously train the model by alternating input data between question answering (QA) and question generation (QG), both in the same model.…”
Section: Joint Model Based Training To Improve Performance Of Neumentioning
confidence: 99%
“…This training framework successfully shown that by exploiting the "duality" of QA and QG improves both QA and QG. Another joint approach for QA and QG is presented in [29]. Authors uses approach presented in [30] to prove hypothesis that good question generation can improve QA performance.…”
Section: Joint Model Based Training To Improve Performance Of Neumentioning
confidence: 99%
See 2 more Smart Citations